CLINICAL AND NEUROLOGICAL MANIFESTATIONS OF DRUG-RESISTANT EPILEPSY AND OPTIMIZATION OF PATIENT TREATMENT - Yo. N. Madjidova (Эпилепсия и пароксизмальные состояния, 2019)
Aim – to study the clinical and neurological manifestations in patients with drug-resistant epilepsy and optimize the therapy. Materials and methods. Fifty patients with drug-resistant epilepsy were examined. Of these, 28 were females and 22 were males; their average age was 32.6±11.4 years. All patients had true pharmacoresistant epilepsy, i. e., the seizures occurred on the background of adequate polytherapy with anticonvulsants; the use of anticonvulsants had no effect on the course of the disease. All patients underwent clinical and neurological examination. The patients were blindly divided into two therapeutic groups: the main group consisted of 25 patients who were prescribed with the combined therapy, which included a biologically active polypeptide at a dose of 10 mg/day for 20 days with a subsequent transition to hopantenic acid (500 mg twice a day for 2 months). The second group did not receive these drugs. For the anticonvulsant therapy, both groups received the combinations of valproic acid (30 mg/kg at two daily doses) and carbamazepine (5 mg/kg at three daily doses). The significance of differences was determined by the paired and unpaired Student’s t-test. The differences were considered statistically significant at p <0.05. Results. The data on the occurrence of subjective and focal neurological symptoms indicated the prevalence of complaints characteristic of general cerebral symptoms in the form of headaches, dizziness, as well as subjective symptoms of cerebral asthenia. In addition, some patients complained of short-term memory impairments. In most cases, drug-resistant epilepsy developed on the background of organic brain damage. In 87.2±6.9% of cases, we encountered a Chvostek sign indicating an increased excitability of the nervous system. Both groups of patients showed positive yet different clinical dynamics: the number of seizures decreased in 40% of patients taking the polypeptide regulator and hopantenic acid, and in 28% of patients in the comparison group (p<0.05). Conclusion. In order to optimize the anticonvulsant therapy, it is recommended to prescribe a combination of valproate and carbamazepine; to increase the efficacy of the combined therapy it is recommended to add the polypeptide regulator and hopantenic acid.